PENGARUH MODEL SIKLUS BELAJAR ABDUKTIF EMPIRIS TERHADAP PEMAHAMAN KONSEP DAN KETERAMPILAN GENERIK SAINS SISWA PADA MATA PELAJARAN FISIKA - Suktomansyah, Andi Muh. (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2021)
This study is an experimental quasi study that aims to examine the effect of abductive empirical cycle model for concepts comprehension and generic science skills of VIII class SMP Negeri 6 Palu. The sample in this study was the VIII A grade students of 30 as experimental group and the VIII B grade students of 30 as control group. Samples were selected used cluster sampling. The experimental group was given abductive empirical cycle model and the control group was given the conventional learning model. Test of concepts comprehension and test of generic science skills were used as instruments in this study. The data was analyzed by using t-test two tailed with significance score 0,05. From the study result it can be concluded that: 1) there was a significance difference in student’s concept comprehension between class taught using abductive empirical cycle model with class taught using conventional model, 2) there was a significance difference in student’s generic science skills between class taught using abductive empirical cycle model with class taught using conventional model.